Fab-mediated binding of drug-dependent antibodies to platelets in quinidine- and quinine-induced thrombocytopenia. - Christie, D J (1985)
Platelets coated with quinine- or quinidine-induced antibodies form rosettes around protein A-Sepharose beads and normal platelets form rosettes about protein A-Sepharose beads coated with these antibodies. These reactions occurred only in the presence of sensitizing drug. Platelets also formed rosettes about protein A-Sepharose beads coated with an anti-PIA1 antibody, but drug was not required. Formation of rosettes between antibody-coated platelets and protein A-Sepharose was inhibited by F(ab')2 fragments of goat antibody specific for the Fc portion of human IgG, while rosette formation between antibody-coated protein A-Sepharose and platelets was inhibited by F(ab')2 fragments directed against the F(ab')2 portion of the IgG molecule. Since binding of IgG to protein A is known to occur via the Fc region, these findings suggest that binding of drug-induced antibodies to platelets occurs at the Fab domains of the IgG molecule.